IMMUNOHISTOCHEMICAL EXPRESSION OF CD44V6 AND P53 STATUS IN BORDERLINE AND MALIGNANT OVARIAN SURFACE EPITHELIAL TUMORS. A CLINICO-PATHOLOGIC STUDY (Iraqi Journal of Medical Sciences, 2016)
Background:Ovarian epithelial cancer is a leading cause of death among gynecological malignancies due mainly to advanced stage at presentation.Objectives:To investigate the expression of CD44v6 and p53 in borderline tumors and malignant ovarian surface epithelial tumors, correlation with clinic-pathological parameters.Methods: A cross sectional study included a total of (101) formalin-fixed paraffin-embedded ovarian tissue blocks; of which (19) cases were borderline tumors and (82) cases were overt ovarian carcinomas. Sections from each block were immunohistochemically stained for CD44v6 and p53.Results:The expression of CD44v6 was higher in ovarian carcinomas (57.3%) than borderline tumors (26.3%) and it was significantly correlated with FIGO stage and histological grade of ovarian carcinomas. p53 was overexpressed significantly in invasive carcinoma compared to borderline tumors, and it was significantly associated with higher grade and FIGO stage of invasive carcinomas.Conclusions: CD44v6 and p53 expressions were correlated with less differentiated, advanced-stage tumor and these markers may be important molecular markers for poor prognosis.Key words:Borderline tumor, ovarian carcinoma, p53, CD44v6.
Keywords: Borderline tumor; ovarian carcinoma; p53; CD44v6